Fueros municipales. Traza de Derecho - Remédios Morán Martín (Medievalista)
The aim of this paper is to present the outlines of the evolution of the Local Law since the early medieval period (7-12th centuries) until the reception of the Common Law in the Iberian Peninsula (13-18th centuries), with special reference to regulation of trades related to the administration of justice in the Castilian-leonese local texts, and especially the evolution of the figure of mayors: from alcaldes de fuero to alcaldes del rey, whose nearest figure in Portugal are Juízes de fora